RETRACTED: Analisis tingkat kecanduan media sosoial pada remaja - Rizki Wulandari; Netrawati Netrawati (IICET (Indonesian Institute for Counseling, Education and Therapy), 2020)
RETRACTION TO:Wulandari, R., & Netrawati, N. (2020). Analisis tingkat kecanduan media sosoial pada remaja. JRTI (Jurnal Riset Tindakan Indonesia), 5(2), 41-46. This article has been retracted by Publisher based on the following reason:The Editor of JRTI (Jurnal Riset Tindakan Indonesia) found the double publication in the article publishing due to the article's content similarity published in http://ppsfip.ppj.unp.ac.id/index.php/ijrice/article/view/347Netrawati, N., Wulandari, R., Karneli, Y., & Syukur, Y. (2020). The Analysis of Social Media Addiction Level on Adolescents. International Journal of Research in Counseling and Education, 4(1), pp. 46-50, doi: http://doi.org/10.24036/00347za0002 One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Reuse of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process